The Role of Philosophy in the De-traumatizing of the Sedimented History - Mažeikis, Gintautas (Eidos. A Journal for Philosophy of Culture, 2025)
The aim of this essay is to answer the question of what philosophy has to offer for the de-traumatization of unreflected history, or the historical sediments of the undifferentiated continuum of our consciousness. Often the historical sediments of everyday anxieties and imaginings have never been subjected to proper critical reflection, and the official narrative is still based on the representation of historical grandeur through which the Real is institutionally defended. The article interprets the Real in Lacanian and Slavoj Žižek’s sense. Whether represented or propaganda, the Real conceals historical traumas, the fears and anxieties that haunt us like an unconscious command. The article argues that a mere critical, hermeneutical, philosophical exposure of a hidden trauma is not enough because it violates dignity. Dignity can be secured through mutual new acts of recognition based on the idea of rational authority. It requires philosophical mediation or mutual equal negotiation: clarifying the conditions of mutual understanding and recognition.